Bulk Metallic Glass Micro Fuel Cell. Issue 12 (26th November 2012) - Sekol, Ryan C.; Kumar, Golden; Carmo, Marcelo; Gittleson, Forrest; Hardesty‐Dyck, Nathan; Mukherjee, Sundeep; Schroers, Jan; Taylor, André D.
<x xml:space="preserve">Abstract</x> A bulk metallic glass (BMG) micro fuel cell displays advantages over traditional micro fuel cell designs in terms of performance and fabrication. The BMG gas flow fields are durable and shock and corrosion resistant, and the Pt‐BMG catalytic layers (including Pt‐BMG nanowires) are promising candidates for use in micro fuel cells. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>